Digital Logistics the Key to Success in the Retail Industry - Phinijphara, Saran; Lakkhongkha, Kritsana (Journal of Industrial Business Administration, 2024)
The modern retail industry is facing challenges from changing consumer behaviors and expectations, demanding more convenience, speed, and variety in accessing products and services.This requires retailers to adapt by applying digital logistics to their business processes to increase efficiency, reduce costs, and better meet customer needs. This research aims to study the concepts,roles, importance, and approaches to applying digital logistics in the retail industry through a review of diverse secondary data sources and content analysis to summarize key knowledge.The findings reveal that digital technologies playing a crucial role in improving logistics processes for retail businesses include logistics information systems such as ERP, WMS, and TMS,which efficiently integrate and manage data; automation technologies like RFID and IoT, used for accurate identification, tracking, and inventory management; intelligent technologies such as AI and Machine Learning, which analyze data and make decisions to optimize operations; and robotics technology for transportation, picking, and sorting of goods, making these processes fast, precise, and highly efficient. These digital logistics technologies bring significant benefits to retail businesses in terms of increased efficiency, cost reduction, responsiveness to customer needs, and competitive advantage.